Randomly Amplified Polymorphic DNA Analysis Of Seagrass Halophila Ovalis. - S., May Pau; A.S., Othman (2002)
Seagrasses are an important component of coastal system, not only important as nursery ground and shelter for many species of marine life, but also have great value in stabilizing and protecting coastlines from erosion due to the physical character of their leaves and root-rhizome system (Sudara et al. 1992)